2013
DOI: 10.1186/cc12800
|View full text |Cite|
|
Sign up to set email alerts
|

Comparisons between intragastric and small intestinal delivery of enteral nutrition in the critically ill: a systematic review and meta-analysis

Abstract: IntroductionThe largest cohort of critically ill patients evaluating intragastric and small intestinal delivery of nutrients was recently reported. This systematic review included recent data to compare the effects of small bowel and intragastric delivery of enteral nutrients in adult critically ill patients.MethodsThis is a systematic review of all randomised controlled studies published between 1990 and March 2013 that reported the effects of the route of enteral feeding in the critically ill on clinically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Several studies in critical care nutrition have not been successful in reaching either target energy or protein delivery (Table 1) [24, 7, 4042]. Notwithstanding that there may be physiological differences in the utilisation of substrates depending on the route and timing of nutrition delivery, strategies to enhance nutrition delivery [62, 63] should be factored into clinical trials where the outcome is dependent upon meeting a target.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…Several studies in critical care nutrition have not been successful in reaching either target energy or protein delivery (Table 1) [24, 7, 4042]. Notwithstanding that there may be physiological differences in the utilisation of substrates depending on the route and timing of nutrition delivery, strategies to enhance nutrition delivery [62, 63] should be factored into clinical trials where the outcome is dependent upon meeting a target.…”
Section: Methodological Challengesmentioning
confidence: 99%
“…A meta-analysis of 15 RCTs showed that small intestinal feeding compared to gastric feeding improved nutritional intake and reduced the incidence of ICU-acquired pneumonia but did not affect other clinically important outcomes [ 64 ]. However, the indications for small intestinal feeding (when?…”
Section: Remaining Areas Of Uncertaintymentioning
confidence: 99%
“…Based on expert opinion, observational studies and small RCTs [37], it has been generally recommended to provide full caloric requirement to critically ill patients [8]. To achieve this goal, interventions to augment caloric intake, such as the implementation of protocols [9, 10], prokineteic agents and postpyloric tube placement [11] have been proposed, even though studies have not demonstrated improvement in clinical outcomes. On the contrary, several observational studies observed better outcome with lower enteral caloric intake [12, 13].…”
Section: Introductionmentioning
confidence: 99%